1996
DOI: 10.1104/pp.110.4.1349
|View full text |Cite
|
Sign up to set email alerts
|

Specific Prenylation of Tomato Rab Proteins by Geranylgeranyl Type-II Transferase Requires a Conserved Cysteine-Cysteine Motif

Abstract: Posttranslational isoprenylation of some small CTP-binding proteins is required for their biological activity. Rab geranylgeranyl transferase (Rab CCTase) uses geranylgeranyl pyrophosphate to modify Rab proteins, i t s only known substrates. Ceranylgeranylation of Rabs is believed t o promote their association with target membranes and interaction with other proteins. Plants, like other eukaryotes, contain Rab-like proteins that are associated with intracellular membranes. However, t o our knowledge, the geran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 62 publications
2
29
0
Order By: Relevance
“…Figure 4A shows that LeRablBmCC, but not BSA, reduced labeling of LeRablB. Similar results were obtained with GST::LeRablCmCC (Yalovsky et al, 1996) and LeRablAmCC (data not shown).…”
Section: Rab-modifying Activity In Plant Cells Is Biochemically More supporting
confidence: 75%
See 3 more Smart Citations
“…Figure 4A shows that LeRablBmCC, but not BSA, reduced labeling of LeRablB. Similar results were obtained with GST::LeRablCmCC (Yalovsky et al, 1996) and LeRablAmCC (data not shown).…”
Section: Rab-modifying Activity In Plant Cells Is Biochemically More supporting
confidence: 75%
“…Second, we show that adding detergent to the Rab GGTase assay increased overall modification of recombinant LeRablB, another feature the plant activity shares in common with mammalian Rab GGTase. Based on the results presented here and in an accompanying paper (Yalovsky et al, 1996), we believe that the Rab-modifying activity under investigation is due to Rab GGTase and not GGTase I or some other nove1 protein prenyl transferase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, farnesyl (15-C) or has not been determined. geranylgeranyl (20-C), isoprenoid prodOver the past few years, changes in the ucts of the mevalonic acid (MVA) pathway, profiles of prenylated proteins during plant are attached to C-proximal cysteine development and the growth of suspension-cultured cells have been documented (Randall et al, 1993;Morehead et al, 1995), and more extensive analyses of the potential role of protein prenyltransferases in regulating progression through the plant cell cycle have been reported (Morehead et al, 1995;Lorraine et al, 1996;Schmitt et al, 1996;Yalovsky et al, 1996).…”
mentioning
confidence: 99%